Effect Of Ammonium And Nitrite Addition On The Anaerobic Treatment Of Palm Oil Mill Effluent - Imas, Siti Nurul Khairaimi (Universiti Sains Malaysia, 2017)
A study of effect of nitrite on anaerobic treatment of palm oil mill effluent (POME) was reported. The optimum nutrient content which is COD:N:P ratio in anaerobic treatment of wastewater was suggested to be 250:5:1. However, nutrient content within POME was not optimal for anaerobic treatment. Adequate nutrients are required to get the effective treatment of waste. The production of Volatile Fatty Acid (VFA) which is important product from anaerobic treatment might be affected with the insufficient nutrient content. Hence, this study suggested that to add nitrite and ammonium in order to increase the nitrogen content within the POME. Theoretically, the presence of nitrite can cause the inhibition of methanogenesis in anaerobic treatment. Therefore, effect of ammonium and nitrite addition on the anaerobic treatment of POME by feeding different source of nitrogen was investigated in this research. Three sets of batch reactors experiments were carried out using the anaerobic treatment of POME from parent reactor which is SBR and fed with ionized water (Reactor 1), ammonium bicarbonate (Reactor 2) and partial effluent of nitrification (Reactor 3) respectively. All these reactors were operated at 1 L working volumeand volume exchange ratio of 20% with 5 day SRT of reactors. The results revealed that addition of nitrite in anaerobic treatment of POME reduce the ammonium removal and biomass activity which in turn leads to lower COD removal. Addition of partial effluent of nitrification inhibits the microbial growth in the Reactor 3 and result in low production of VFA. While addition of ammonium in the wastewater biological treatment can enhance the biomass growth. The increasing biomass growth in Reactor 3 will increase the efficiency of anaerobic treatment. Hence, addition of ammonium in order to increase the nitrogen level in the wastewater is a suitable nitrogen source for POME but not for nitrite.